Pupils’ Literacy Problems in the Essays of Lithuanian Language and Literature State Matura Examinations: Gaps in the Knowledge of Syntax - Bučienė, Laimutė (Acta Paedagogica Vilnensia, 2021)
Based on the syntactic analysis of the essays composed in the course of the matura examination in 2019, the article seeks to answer the following major questions: How well are 12th grade pupils capable of observing the syntactic norms while writing a fluent text? Which syntactic phenomena do pupils find the most troublesome?A quantitative study revealed that the pupils have an insufficient knowledge of syntactic norms. Pupils find case government, the combinability of words, the choice of word forms in a phrase and in a sentence the most troublesome. The greatest syntactic problem is the incorrect use of cases. What is most obvious and problematic concerning case-related mistakes is the use of the instrumental case to express a state instead of the second component of double cases. The expression of the indefinite amount of things and the whole is also rather troublesome (the use of the accusative case instead of the genitive case expressing an indefinite amount or a part). In their essays, pupils often make mistakes in the use of the gerund. The mistakes related to the composition of the complex sentence are also rather numerous.It should be noted that the teaching of language system-related topics should pay adequate attention to the practical issues of language teaching as well as to tasks focusing on the correct usage of the spoken and written language.The errors made by 12th grade pupils show that it is essential to improve the skills of the correct usage of syntactic constructions in the final grades with due regard to the individual needs of pupils and the class.
Keywords: literacy; pupil; essay; syntax; state matura examination